Investigating Salt Tolerance in Melon During Germination and Early Seedling Stages - Peng Liu; Chao Gao; Yinan Gao; Chongqi Wang; Zigao Jiao; Aolin Xu; Yumei Dong; Jianlei Sun (Horticulturae)
This study aimed to investigate the correlation between salt tolerance during the germination and seedling stages in melons by analyzing 10 melon varieties under NaCl stress during germination and seedling stages. We found that 200 mM is the appropriate concentration for screening salt-tolerant germplasm in melons. Salt stress led to a decline in germination and seedling growth parameters, while antioxidant enzyme activities and osmotic substance contents significantly increased. Specifically, the activities of CAT and SOD increased by up to 27.22-fold and 6.35-fold, respectively, and soluble protein and proline contents increased by up to 1.03-fold and 1.05-fold, respectively. Varietal differences in salt tolerance traits were observed. Correlation and principal component analyses revealed that 6 germination indicators could be consolidated into 1 comprehensive indicator, accounting for 79.225% of the variance, while 16 seedling-stage indicators were reduced to 3 comprehensive indicators, with a cumulative contribution rate of 75.089%. Membership function and cluster analyses categorized the 10 varieties into 3 groups at both stages, identifying ‘Xindongfangmi’ and ‘Jinyuliuxing’ as salt-tolerant varieties. Additionally, a significant positive correlation (r = 0.834) was found between the comprehensive membership function values of germination and seedling stages. These results provide a scientific basis for assessing melon salt tolerance, indicating that germination-stage salt tolerance may predict seedling-stage salt tolerance. By utilizing PCA, comprehensive evaluation, and cluster analysis of relevant indicators under salt stress during the germination period of melon, the salt tolerance of the seedling stage can be quickly identified. The implementation of rapid salt tolerance screening at the germination stage can facilitate the selection of salt-tolerant germplasm and the development of salt-tolerant melon varieties.